Antimicrobial treatments with chitosan microencapsulated angelica (Angelica archangelica) and marsh Labrador tea (Rhododendron tomentosum) supercritical CO2 extracts in linen-cotton jacquard woven textiles - Kunnas, Susan; Tienaho, Jenni; Holmbom, Thomas; Sutela, Suvi; Liimatainen, Jaana; Kaipanen, Kalle; Jääskeläinen, Ritva; Sääski, Soile; Korpinen, Risto I (SAGE, 2024)
In this study antimicrobial linen-cotton jacquard textiles were manufactured using green chemistry methods. The functionalization of the fabrics was executed by impregnating chitosan microencapsulated bio-based oils from angelica (Angelica archangelica L.) (AAC) and marsh Labrador tea (Rhododendron tomentosum Harmaja) (MLTC) obtained with pilot scale supercritical carbon dioxide extraction. The chemical compositions of the extracts of angelica and marsh Labrador tea were analyzed by a combination of gas chromatography and mass spectrometry. The antimicrobial activities of the extracts, AAC and MLTC microcapsules, and the microencapsulated textiles (AAC and MLTC textiles) were analyzed against gram-positive Staphylococcus aureus and gram-negative Escherichia coli bacteria, dimorphic yeast Candida albicans and filamentous mold Aspergillus brasiliensis. The AAC textile proved 40% inhibition against S. aureus, whereas the MLTC textile demonstrated 43.8% and 51.7% inhibition against both S. aureus and E. coli, respectively. Although the chitosan shell material itself indicated mild activity against both bacterial strains, the extracts increased the antibacterial activities in microencapsulated textiles. In addition, the antifungal impact of the MLTC textile was demonstrated against A. brasiliensis. According to the Fourier transform infrared spectroscopy with attenuated total reflection and field emission scanning electron microscopy analyses, covalent bonding between the microcapsules and textile fibers was established with citric acid as a cross-linker. The antimicrobial activity was also shown to persist in the MLTC textiles after six domestic washing cycles.
Keywords: GC-MS; antimicrobial activity; microencapsulation; textile functionalization; plant extracts; natural compounds; supercritical carbondioxide extraction